Competing Logics in the Affordable Housing Industry: A Comparative Analysis of How Various Types of Professionals in the For-Profit and Non-Profit Sectors Conceptualize Their Work and that of Their Companies. Issue 2 (15th March 2023) - Read, Dustin C.; Sedgwick, Donna
ABSTRACT: For-profit and non-profit companies develop, own, and manage a majority of the affordable housing in the United States. Both types of enterprises rely on developers, asset managers, property managers, and resident service coordinators to strike a balance between financial and social goals. These conditions raise questions about how individuals employed in different sectors and in different professional roles perceive this balancing act. Such questions are interesting because the field logic of the affordable housing industry could encourage those working in various capacities on behalf of for-profits and non-profits to have similar perceptions of these issues, whereas sector and professional logics could encourage them to have perceptions that are dissimilar. This study explores these alternative propositions. Results suggest more pronounced perceptual cleavages exist across professions than across sectors in the U.S. affordable housing industry – and that representatives of for-profits and non-profits alike conceptualize their work in ways consistent with institutional logics theory.